Proyecto de factibilidad para la creación de una empresa productora de tabacos sin filtro “chamico” y su comercialización en la ciudad de Loja - Paz Sisalima, Daniel (2015)
The snuff has mainly two advantages over other drug consumption: it is socially acceptable and legal consumer is what helps make it more widely used Another problem is when the person addicted to snuff stop consuming, some mental and physical disorders, such as occur in nature: anxiety, irritability, nervousness, insomnia, tremors, etc. How rebut or reduce risks inherent in this market entrepreneurship (snuff) in the country? A suitable tool constituent studies Feasibility, the same that will evaluate commercial, technical, legal and financial business idea, always trying to find the best alternative to trying to market and leverage strengths that have this type of product that has come prepared and consumed by our ancestors and we intend to expand the market. Thus, in order to promote the development and growth of our city and solve the problem explained it was thought advisable to create an automotive mechanics. Through the National University of Loja and commitment to the community is to conduct research work entitled: "Feasibility Project for the creation of a producer of snuff unfiltered" fireweed "and its commercialization in the city of Loja ". This research has as its main objective: Determine the feasibility of implementing a producer and marketer of seafood Skewers Company in the city of Loja. And the complete analysis of the project requires the realization of the specific objectives: market research, technical study, administrative and legal study, economic, financial study and finally the evaluation. To study the following research methodology was used: the deductive method yielded valid conclusions determining the feasibility or project creation and analytical descriptive method this method was used during the development of all research. In the results a survey was applied to both plaintiffs City Loja to determine product acceptance in the market. Within the discussion studying market where demand was established was performed; being able to obtain the unsatisfied demand is 4780804 units of tobacco for the first year, then the marketing plan, pricing, place and product advertising is established; The technical study the size and location of the plant is detailed; In the administrative and legal study of the company facilitates determining business group, the constitution, organization and functions manuals. In the financial investment necessary study notes to implement the project the same which is $ 28,255.71 US dollars. Finally the assessment for which the following indicators are analyzed was performed: Net Present Value of $ 68,506.55; Internal Rate of Return of 52.50%; Benefit Cost Ratio is 1.43 for every dollar invested company earns 0.43 cents; Capital Recovery Period is 2 years, 5 months and 23 days; Sensitivity analysis indicates that the project supports an increase in the cost of 24.55% for a total of 0.98% and a sensitivity analysis on the decrease in revenues of 18.10% for a total of 0.99% so the project is feasible, the conclusions and recommendations so determined, accompanied by the literature consulted with their respective annexes.